SHARIA MANAGEMENT AND BENEFITS FOR FOOD TRADERS - Emmy Dwi Setyaningsih (Al-Idarah, 2022)
The development and competition of the business world in the current era of globalization is getting higher. This study aims to determine the marketing strategy of basic food traders. The method used is qualitative based on observation, interviews, and documentation. The results showed, (a). The marketing strategy of this basic food business has implemented a sharia marketing strategy that is honest, trustworthy, and communicative. (b). business development strategy of basic food sellers in improving the welfare of the community by providing affordable and competitive prices, as well as providing maximum service to consumers, establishing harmonious relationships with internal and external parties of the company, and trying hard and earnestly.Keywords: Management Strategy, Basic Food Business, Islamic Economy.